logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Browse Questions
Ad
Home  >>  JEEMAIN and AIPMT  >>  Mathematics  >>  Trignometry
0 votes

If $\tan^{-1}\large\frac{1}{a-1}$$=\tan^{-1}x+\tan^{-1}(x+1)=\tan^{-1}3x$ is

$\begin{array}{1 1}(a)\;\large\frac{a}{2}&(b)\;a^3\\(c)\;a^2-a+1&(d)\;a^2+a-1\end{array}$

Can you answer this question?
 
 

1 Answer

0 votes
We have $\tan^{-1}\large\frac{1}{a-1}$$=\tan^{-1}\large\frac{1}{x}$$+\tan^{-1}\large\frac{1}{a^2-x+1}$
$\Rightarrow \tan^{-1}\large\frac{1}{a-1}$$=\tan^{-1}\large\frac{1/x+1/a^2-x+1}{1-1/x(a^2-x+1)}$
$\Rightarrow \large\frac{1}{a-1}=\frac{a^2+1}{(a^2+1)(x-x^2-1)}$
$x^2-x(a^2+1)+1+(a-1)(a^2+1)=0$
$x^2-a^2-(a^2+1)(x-a)=0$
$(x-a)(x+a-a^2-1)=0$
$x=a$
Or $x=a^2-a+1$
Hence (c) is the correct option.
answered Nov 15, 2013 by sreemathi.v
 

Related questions

Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...